Perancangan Kawasan Slamet Riyadi Surakarta Segmen Ngapeman Hingga Gladak Sebagai Pedestrian Mall - Aulia Kurnia Putri; Ofita Purwani; Tri Joko Daryanto (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2017)
AbstractSlamet Riyadi street is one of Surakarta main roads which has a role as network connectivity withinadjacent district. Slamet Riyadi street whose existence line up with the history of Surakarta, housesseveral historical building heritage along its road. The structures alongside Slamet Riyadi street havemany different functions, one of them is commerce and trade purpose which ample mostly on thesection of Ngapeman through Gladak. Ngapeman through Gladak section has a prospect to becomean example of a thriving pedestrian mall. A pedestrian mall is capable to revive the active use ofSlamet Riyadi street. A pedestrian Mall in Slamet Riyadi street can be used as a means to promotewalking habit for the citizens by providing a space for pedestrian. With an addition of rapid transitfacility, people in the city will be convinced to take a stroll on its pedestrian way, thus provide anactive use for the district. A pedestrian Mall promotes diverse activities, which include daily orperiodic activity, to ensure frequent visit. A pedestrian mall provides consumption and commerceactivity for people to enjoy as a day-to-day attraction. A pedestrian Mall also encourages communities to use the space to organize eventswhich utilize the outdoor concept of pedestrian mall such as exhibitions, festivals, and fairs. Thequality of public space will improve with the addition of public amenity and public art within the area.Certain mural art and vine pergola become attractive objects in the area whilst the public amenityaddition can furnish the overall pedestrian mall usage.  Keywords: slamet riyadi, pedestrian, pedestrian mall, public space, outdoor space